Telemedicine: An Innovative Twist to Primary Health Care in Rural Bangladesh - Md. Hafiz Iqbal (SAGE Publishing, 2020)
Background: Health care service is worsening in the remote villages due to less complete and further away of healthcare facilities and service and makes this service costs compared to those of urban people. Telemedicine service provides a potential solution regarding this particular issue. This study provides empirical evidence of the benefits package consists of hypothetical telemedicine service and evaluates the economic benefit of telemedicine service. Methods: The study measures marginal willingness-to-pay (MWTP) responses to policy change on a sample (n = 203) observations. A randomized conjoint experiment has conducted in 7 remote villages of 3 coastal districts of the southwest coastal region of Bangladesh. Each respondent ranks 3 options-two hypothetical alternatives and the telemedicine status quo scheme. The level of attributes-payment for telemedicine service, sample collection from home, medicine delivery to home, capitation through online technology, service delivery frequency, and blood pressure and glucose measure at home-are randomly and jointly assigned to the 2 alternatives. Results and Conclusions: Coastal villagers would like to pay more in option 4 and above. The lower payment for telemedicine service does not necessarily imply low demand for telemedicine, as the findings from MWTP illustrate potential demand for telemedicine in coastal villages in Bangladesh.